A kind of hydrogen ion battery based on carbonate and preparation method thereof

By using alkali carbonate or bicarbonate containing variable valence transition metal elements in the battery as active material and using the proton jump mechanism, the existing batteries have high cost and low cycle times in large-scale energy storage applications, and the electrochemical energy storage effect with low cost, long life and high power density is achieved.

CN119133639BActive Publication Date: 2025-03-04TESCHAL SCI (SUZHOU) CO LTD

Patent Information

Application Number
CN202411585704.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-04
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

Existing batteries have high costs and low cycle times for large-scale energy storage purposes, and are limited by mineral yields, making it difficult to achieve low-cost, long-life, and high-power density electrochemical energy storage.

Method used

A carbonate-based hydrogen ion battery is used, and basic carbonate or bicarbonate containing variable valence transition metal elements are used as the positive and negative electrode active materials. Carbonate or bicarbonate buffer solution is added to the aqueous electrolyte to achieve the migration of hydrogen ions and the balance between substances and charges through a proton jump mechanism.

Benefits of technology

It realizes electrochemical energy storage with low cost, high charge and discharge cycle times, long service life and large charge and discharge power, and overcomes the high cost, low cycle times and safety hazards of existing batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133639B_ABST
    Figure CN119133639B_ABST
Patent Text Reader

Abstract

The present invention relates to a carbonate-based hydrogen ion battery and a preparation method thereof. The positive electrode active material and the negative electrode active material of the hydrogen ion battery are basic carbonates or bicarbonates containing variable-valence transition metal elements, and the aqueous electrolyte thereof is a buffer solution containing soluble carbonates or bicarbonates. Compared with the prior art, the hydrogen ion battery of the present invention has a high efficiency in the process of charging and discharging, and the hydrogen ions migrate in the positive / negative electrode active materials and the electrolyte, and CO3 2‑ and HCO3 ‑ The transformation is achieved to realize the material and charge balance of the active material during the redox electrochemical reaction; low-cost, long-life, and high-power density electrochemical energy storage is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrochemical energy storage, and in particular relates to a carbonate-based hydrogen ion battery and a preparation method thereof, which are used in the field of large-scale electric energy storage and realize electrochemical energy storage with low cost, long life and high power density. Background Art

[0002] Although lithium iron phosphate batteries do not require the use of the relatively expensive cobalt element, which greatly reduces the cost of lithium-ion batteries, they are still relatively expensive for large-scale energy storage purposes, have a low number of cycles, and are limited by the production of minerals such as lithium and cobalt, which restricts their further application in the field of large-scale energy storage.

[0003] Therefore, sodium-ion batteries have been widely studied. However, the cost reduction of organic electrolytes compared to lithium-ion batteries is lower than the reduction in battery performance, and its economic efficiency needs to be further improved. Therefore, aqueous sodium-ion batteries have received much attention.

[0004] However, since the radius of sodium ions is significantly larger than that of lithium ions, the insertion and extraction of sodium ions in electrode materials affects the stability of the materials and reduces the performance of sodium ion batteries.

[0005] In patent CN201980022874.8, Maher F. El-Cadi et al. from the University of California proposed using iron-based or zinc-based layered compounds as the first electrode and a hydroxide containing nickel hydroxide as the second electrode to construct a redox and ion adsorption electrode and energy storage device. However, the energy storage density of the capacitor mechanism based on ion adsorption is low, which restricts practical applications. Summary of the invention

[0006] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a carbonate-based hydrogen ion battery and a preparation method thereof with low cost, high number of charge and discharge cycles, long service life, and high charge and discharge power.

[0007] The object of the present invention can be achieved by the following technical scheme: a carbonate-based hydrogen ion battery, wherein the positive electrode active material and the negative electrode active material of the hydrogen ion battery are basic carbonates or bicarbonates containing variable-valence transition metal elements, and the aqueous electrolyte thereof is a buffer solution containing soluble carbonates or bicarbonates;

[0008] The oxidation-reduction electrochemical reaction of the active elements in the hydrogen ion battery during the charge and discharge process is:

[0009] XHCO3 – e => X'CO3 + H + (a)

[0010] X'CO3 + H ++ e => XHCO3(b)

[0011] Wherein, X and X' are corresponding basic cations of adjacent valence states containing variable valence transition metal elements (iron, manganese or nickel);

[0012] During the charge and discharge process of the primary battery, electrochemical reactions (a) and (b) occur simultaneously at the positive and negative electrodes, respectively.

[0013] During the charge and discharge process of the primary battery, hydrogen ions (protons) migrate between the positive / negative electrode materials and the electrolyte, and CO3 2- and HCO3 - to achieve material and charge balance of the active species during the redox electrochemical reaction.

[0014] The variable valence transition metal element is iron, manganese or nickel.

[0015] Furthermore, the variable valence transition metal element is Fe; that is, X=Fe(II) and X'=Fe(III), forming a Fe(III / II) electrode pair, which is used as the negative electrode active material of the battery. The redox electrochemical reaction of the active material during the charge and discharge process is:

[0016] Fe(II)-HCO3 – e => Fe(III)-CO3 + H + (1a)

[0017] Fe(III)-CO3 + H + + e => Fe(II)-HCO3(1b)

[0018] Furthermore, the negative electrode active material of the hydrogen ion battery is an alkaline carbonate or bicarbonate containing iron, and the positive electrode active material of the hydrogen ion battery is an alkaline carbonate or bicarbonate containing manganese or nickel.

[0019] Furthermore, the negative electrode active material of the hydrogen ion battery is a basic carbonate or bicarbonate containing iron and magnesium elements, forming an Fe(III / II) electrode pair; the chemical formula of the negative electrode material of the basic carbonate or bicarbonate containing iron and magnesium elements is preferably:

[0020] Fe(III)-CO3:[Mg x Fe(III) 1+y (OH) 2(1+x+y) ] (CO3) (1+y) / 2 , where 0 <x≤10,0≤y≤1;

[0021] Considering the stability and economy of the compound, preferably: 0.5≤x≤4.5; 0≤y≤0.5;

[0022] Alternatively, Fe(II)-HCO3:[Mg x Fe(II)Fe(III) y (OH) 2(1+x+y) ] (HCO3) y , where 0 <x≤10,0<y≤1;

[0023] Considering the stability and economy of the compound, preferably: 0.5≤x≤4.5; 0≤y≤0.5.

[0024] Furthermore, the variable valence transition metal element is Mn; that is, X=Mn(III) and X'=Mn(IV), Mn(IV / III) constitutes an electrode pair, and the redox electrochemical reaction of the active material during the charge and discharge process is:

[0025] Mn(III)-HCO3 – e => Mn(IV)-CO3 + H + (2a)

[0026] Mn(IV)-CO3 + H + + e => Mn(III)-HCO3(2b)

[0027] Furthermore, the positive electrode active material of the hydrogen ion battery is a basic carbonate or bicarbonate containing manganese and magnesium elements, constituting a Mn(IV / III) electrode pair, and the chemical formula of the positive electrode material containing the basic carbonate or bicarbonate containing manganese and magnesium elements is preferably:

[0028] Mn(IV)-CO3:[Mg x Mn(IV)(OH) 2(1+x) ] CO3, of which 0 <x≤10;

[0029] Considering the stability and economy of the compound, preferably: 0.5≤x≤4.5;

[0030] Alternatively, Mn(III)-HCO3:[Mg x Mn(III) (OH) 2(1+x) ] HCO3, of which 0 <x≤10;

[0031] Taking into account the stability and economy of the compound, preferably: 0.5≤x≤4.5.

[0032] Further, the variable-valence transition metal element is Ni; that is, X = Ni(II) and X’ = Ni(III), and Ni(III / II) forms an electrode pair. As the negative electrode active material of the battery, the redox electrochemical reaction of the active material during charge and discharge is as follows:

[0033] Ni(II)-HCO3 – e => Fe(III)-CO3 + H + (3a)

[0034] Ni (III)-CO3 + H + + e => Fe(II)-HCO3(3b)

[0035] Further, the positive electrode active material of the hydrogen ion battery is a basic carbonate or bicarbonate containing nickel and magnesium elements, forming a Ni(III / II) electrode pair. The chemical formula of the positive electrode material of the basic carbonate or bicarbonate containing nickel and magnesium elements is preferably:

[0036] Ni(III)-CO3:[Mg x Ni(III) 1+y (OH) 2(1+x+y) (CO3) (1+y) / 2 , where 0 < x ≤ 10, 0 ≤ y ≤ 1;

[0037] Considering the stability and economy of the compound, it is preferably: 0.5 ≤ x ≤ 4.5; 0 ≤ y ≤ 0.5; or, Ni(II)-HCO3:[Mg x Ni(II)Ni(III) y (OH) 2(1+x+y) (HCO3) y , where 0 < x ≤ 10, 0 < y ≤ 1; Considering the stability and economy of the compound, it is preferably: 0.5 ≤ x ≤ 4.5; 0 ≤ y ≤ 0.5;

[0038] Or partially replace Ni with Fe to further reduce costs:

[0039] Ni(III)-CO3:[Mg x Ni(III)Fe(III) y (OH) 2(1+x+y) (CO3) (1+y) / 2 , where 0 < x ≤ 10, 0 ≤ y ≤ 1;

[0040] Considering the stability and economy of the compound, it is preferably: 0.5 ≤ x ≤ 4.5; 0 ≤ y ≤ 0.5;

[0041] ​​Ni(II)-HCO3: [Mg x Ni(II)Fe(III) y (OH) 2(1+x+y) (HCO3) y , where 0 < x ≤ 10, 0 < y ≤ 1; considering the stability and economy of the compound, preferably: 0.5 ≤ x ≤ 4.5; 0 ≤ y ≤ 0.5. Further, the positive electrode active material and the negative electrode active material of the hydrogen ion battery may also be added with basic carbonates or bicarbonates containing Al or Zn elements, and the molar ratio of Al: Zn: X is 0~1: 0~1: 1, and the variable valence transition metal element X is Fe, Mn or Ni. In addition, more element options can be considered to improve the stability performance of the active material, such as Ca, Cr, etc.

[0042] Further, the aqueous electrolyte contains carbonates with a concentration of 0.01~5 mol / L or bicarbonates with a concentration of 0.01~5 mol / L, or a mixture of both; the corresponding cations are Na + , K + one of them or a mixture of both, and the molar ratio of Na + , K + is 0~1: 1~0.

[0043] Further, the basic carbonate or bicarbonate containing a variable valence transition metal element may also be added with pillared anions, such as benzenesulfonate, benzene disulfonate or alkylbenzenesulfonate and the corresponding Na + , K + cations, and the molar ratio of Na + , K + is 0~1: 1~0.

[0044] Further, the basic carbonate or bicarbonate containing a variable valence transition metal element is also mixed with a conductive carbon material, and the mass ratio of the basic carbonate or bicarbonate containing a variable valence transition metal element to the conductive carbon material is 1: 0.01~0.5;

[0045] The conductive carbon material is one or a mixture of two of acetylene black and graphite, and the molar ratio of acetylene black and graphite is 0~1: 1~0.

[0046] In the electrolyte, soluble nitrates and sulfates can be added to improve the conductivity and low-temperature performance of the electrolyte, and the corresponding cations are Na + , K + one of them or a mixture of both (Na + , K +The molar ratio is 0~1:1~0), the nitrate concentration is 0~5mol / L, and the sulfate concentration is 0~5mol / L.

[0047] The present invention also provides a method for preparing a carbonate-based hydrogen ion battery, wherein the positive electrode active material and the negative electrode active material are respectively mixed with an aqueous electrolyte, and are respectively coated on a carbon electrode material current collector (selected from one or a composite of conductive graphite plate, graphite felt, graphite mesh, and carbon cloth) to obtain a positive electrode material and a negative electrode material, and the positive electrode material and the negative electrode material are separated by a corrosion-resistant porous material to obtain a single battery, and a plurality of single batteries are stacked and assembled in parallel or curled into a columnar shape to obtain a battery core pack, which is then packaged with a corrosion-resistant battery shell to obtain a hydrogen ion battery pack.

[0048] The corrosion-resistant porous material separating the positive electrode material and the negative electrode material is a composite of one or more of a porous polymer film, a non-woven fabric, a glass fiber cloth, and a filter paper. The battery lead wire passes through the corrosion-resistant shell to connect the positive / negative electrode current collector, and the corrosion-resistant shell is also provided with a liquid injection port and a safety valve. Compared with the prior art, the present invention has the following beneficial effects:

[0049] (I) The present invention uses cheap basic carbonate / bicarbonate of elements such as iron and manganese as the basis to develop a proton shuttle battery using the "proton hopping" mechanism (also known as the "Grotthuss mechanism"). Proton hopping is the process by which "excess" protons or proton "deficiencies" diffuse through the hydrogen bond network of water molecules or other hydrogen-bonded liquids, involving adjacent molecules through the formation and accompanying breaking of covalent bonds. Since protons (H + The "ionic radius" of protons (protons) is smaller than that of lithium ions, thus avoiding damage to electrode materials during the shuttling process and increasing the number of battery cycles; the "proton hopping" mechanism also improves the conductivity of the material and increases the power density of the battery during charging and discharging.

[0050] (II) The present invention utilizes the variable valence characteristics of transition metal elements such as iron, manganese, and nickel to develop a carbonate-based hydrogen ion battery suitable for large-scale low-cost chemical energy storage. It overcomes the problems of low charge and discharge cycles of lead-acid batteries, hydrogen evolution corrosion, and heavy metal environmental pollution during the recovery process; it overcomes the problem of lithium batteries using organic electrolytes, which have potential safety hazards such as fire and combustion, and the problem of using high-priced metal elements such as nickel, cobalt, and lithium with limited production; it also overcomes the problem of damage to electrode materials during the embedding, de-embedding, and shuttling of sodium ions in sodium ion batteries, thereby reducing the number of cycles and service life of the battery.

[0051] (iii) The battery of the present invention has the advantages of low cost, high number of charge and discharge cycles, long service life, and high charge and discharge power. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 It is the pH-potential diagram of Fe, Mn and Ni elements in water system;

[0053] Figure 2 This is the cycle test diagram of Example 3;

[0054] Figure 3 This is the cycle test diagram of Example 7. DETAILED DESCRIPTION

[0055] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.

[0056] The present invention takes into account that lithium ions have a small ionic radius, and the only ions smaller than lithium ions are protons (hydrogen ions). Only batteries based on the shuttle of protons (hydrogen ions) can achieve better cycle performance than lithium ions. From this perspective, sodium ion batteries are obviously difficult to achieve.

[0057] In essence, the redox flow battery is also a proton (hydrogen ion) shuttle battery. Through the shuttling of protons on both sides of the proton exchange membrane, the material and charge balance of the positive and negative electrolytes is achieved. This is also an important reason why the redox flow battery has a good service life and is also an important reference basis for the present invention.

[0058] The structure of current lithium-ion battery positive electrode materials: (a) polyanion structure of lithium iron phosphate, (b) layered structure of lithium cobalt oxide or ternary lithium.

[0059] Various phosphate materials for aqueous sodium ion batteries have defects such as poor conductivity and unsatisfactory cycle times. The reason is that phosphates are easily hydrolyzed into hydrogen phosphate under neutral or acidic conditions, and phosphates and multivalent metal ions are easy to form complexes that dissolve in water, destroying the structure of active materials. The insoluble transition metal basic carbonate used in the present invention effectively overcomes this problem.

[0060] Considering that compared with lithium-ion batteries using organic electrolytes, the general rated voltage is 3.2~3.8V; and batteries using aqueous electrolytes are limited by the electrochemical window of water, such as all-vanadium liquid flow batteries, whose rated voltage is mostly 1.2V. Hydrogen or oxygen evolution reactions are likely to occur beyond this voltage range.

[0061] The battery voltage of aqueous electrolyte is only 1 / 3 or lower than that of lithium-ion battery using organic electrolyte. Therefore, if aqueous electrolyte is used in development, material cost must be reduced as much as possible.

[0062] Considering that iron, manganese and nickel are abundant in reserves and are transition metal elements with relatively low utilization costs per mole of chemical state, the present invention uses compounds of these three metal elements as active material components.

[0063] The present invention creatively proposes a static battery that realizes proton (hydrogen ion) shuttle battery in the solid active components of the positive / negative electrodes and the electrolyte. Compared with the redox flow battery, the battery structure is greatly simplified, and no proton exchange membrane, circulation pump, etc. are required. The problem of bypass current of the flow battery that reduces energy efficiency is overcome. It is easy to operate and maintain, and overcomes the problems of high cost and limited contact area of ​​proton exchange membrane.

[0064] The positive / negative active materials of the hydrogen ion battery of the present invention are basic carbonate / bicarbonate containing transition metal elements (Fe, Mn, Ni), and the aqueous electrolyte is a carbonate / bicarbonate buffer solution; the redox electrochemical reaction of the active material during the charge and discharge process is:

[0065] XHCO3 – e => X'CO3 + H + (a)

[0066] X'CO3 + H + + e => XHCO3(b)

[0067] Wherein X and X' are corresponding basic cations of adjacent valence states containing the same variable-valence transition metal element (Fe, Mn, Ni), and the valence state of the metal element in X' is higher than that in X.

[0068] During the charging and discharging process of the primary battery, the electrochemical reactions (a) and (b) are carried out simultaneously at the positive and negative electrodes, respectively.

[0069] Scientific research shows that the "proton hopping" phenomenon (also known as the "Grotthus mechanism") occurs during the conduction of aqueous solutions. Proton hopping is the process in which "excess" protons or proton defects diffuse through the hydrogen bond network of water molecules or other hydrogen-bonded liquids, involving adjacent molecules through the formation and accompanying covalent bond breakage. This principle is utilized in the present invention, and the migration of hydrogen ions in the positive / negative electrode materials and electrolytes, as well as CO3 2- and HCO3 - to achieve material and charge balance of the active species during the redox electrochemical reaction.

[0070] The present invention takes into account that if anions (such as sulfur SO4 2- 、NO3 - , Cl - Br -The embedding / extraction mechanism of protons in layered double hydroxide complex salts may cause damage to the material structure and performance; the proton embedding / extraction mechanism using the "proton hopping" mechanism can avoid damage to the material structure and performance; and the proton embedding / extraction mechanism can only be achieved by using polybasic weak acids as anions, such as carbonic acid, phosphoric acid, and hydrosulfuric acid, but hydrosulfuric acid easily forms extremely insoluble precipitates with metal ions such as Fe(II) and Mn(II), and phosphoric acid easily forms soluble complexes with Mn(IV), thereby eliminating them; the present invention uses the CO3 of carbonate 2- and HCO3 - transformation mechanism.

[0071] The iron / manganese primary cell potential of the hydrogen ion battery of the present invention is within the oxygen evolution potential and graphite hydrogen evolution overpotential window, which avoids the occurrence of hydrogen and oxygen evolution reactions during the battery's charge and discharge process, and achieves higher energy efficiency in the battery's charge and discharge cycle.

[0072] In a preferred embodiment, the hydrogen ion battery of the present invention uses a basic carbonate / bicarbonate active material containing a Mn (IV / III) electrode pair and a conductive carbon material that are fully mixed to form the positive electrode material of the original battery, and uses a basic carbonate / bicarbonate active material containing a Fe (III / II) electrode pair and a conductive carbon material that are fully mixed to form the negative electrode material of the original battery. The voltage of the original battery is about 0.7V.

[0073] In a preferred embodiment, the hydrogen ion battery of the present invention uses an alkaline carbonate / bicarbonate active material containing a Ni (III / II) electrode pair and a conductive carbon material as a fully mixed primary battery positive electrode material, and uses an alkaline carbonate / bicarbonate active material containing a Fe (III / II) electrode pair and a conductive carbon material as a fully mixed primary battery negative electrode material, and the primary battery voltage is about 1.1V.

[0074] like Figure 1 As shown in the figure, it is the pH-potential diagram of Fe, Mn and Ni elements in water system. It can be seen from the figure:

[0075] The electrode potential of the Mn(IV / III) couple is lower than the standard oxygen potential, so oxygen evolution can be avoided during charging, thereby improving charge and discharge energy efficiency;

[0076] Although the electrode potential of the Ni(III / II) pair is higher than the standard oxygen potential, it is still lower than the oxygen overpotential (graphite), and oxygen evolution can be avoided during charging, thereby improving charge and discharge energy efficiency;

[0077] The electrode potential of the Fe(III / II) couple is higher than the standard hydrogen potential, so hydrogen evolution can be avoided during charging, thereby improving charge and discharge energy efficiency;

[0078] The potential trend lines of the Mn (IV / III) electrode pair and the Fe (III / II) electrode pair are substantially parallel in the range of pH=7.5-13, so the voltage of the carbonate (Fe, Mn) hydrogen ion battery developed by the present invention is easy to maintain stability and is not affected by the change of the pH of the electrolyte in this range;

[0079] The potential trend lines of the Ni (III / II) electrode pair and the Fe (III / II) electrode pair are basically parallel in the range of pH = 7.5 to 13. Therefore, the voltage of the carbonate (Fe, Ni) hydrogen ion battery developed in the present invention is easy to maintain stable and is not affected by changes in the pH of the electrolyte in this range.

[0080] The following embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments; the hydrogen ion battery formed by adding other elements including but not limited to aluminum, zinc, chromium and other elements and their carbonates, hydroxides and other compounds to the active material to form layered carbonate / bicarbonate compounds is also within the protection of the present invention.

[0081] The application scenario of the present invention takes large-scale electric energy storage as the main application scenario, that is, it mainly considers the unit energy storage cost, energy efficiency, number of cycles and safety, and can appropriately reduce the field of energy density requirements; it is benchmarked against lead-acid battery energy storage systems, lithium battery energy storage systems, all-vanadium liquid flow battery energy storage systems, etc., and uses them as comparison examples; it is different from the fields of movable equipment such as automobiles and electronic product energy storage systems that have higher requirements for energy density.

[0082] The embodiments of the present invention only list representative component ratios. Considering that the chemical properties of the double salts are similar, the influence of the changes in the component ratios on their chemical properties is small. Therefore, relevant professionals can adjust the compound components according to the embodiments to obtain similar solutions, or due to errors in the preparation process or test methods, the composition of the prepared active material is close to the composition ratio of the present invention, which should be within the scope of protection of the present invention. That is to say: hydrogen ion batteries with similar principles composed of iron, manganese, and nickel metal elements with similar properties are all within the scope of protection of the present invention, and there is no need to enumerate them one by one.

[0083] Example 1

[0084] An electrode material for a carbonate (Fe, Mn) hydrogen ion battery is prepared by the following method:

[0085] Prepare 1.0 L of an aqueous solution containing 3.0 mol / L Mg(NO3)2, 1.0 mol / L Fe(NO3)2, and 1.0 mol / L Fe(NO3)3; add 25 g of graphite powder and 15 g of acetylene black under sufficient stirring to form a suspension, then add 5.5 L of an aqueous solution containing 1.0 mol / L Na2CO3 under nitrogen protection and sufficient stirring, filter under nitrogen protection and sufficient stirring, separate the precipitate and wash it once with deionized water, and filter the precipitate to obtain a negative electrode material; the precipitate contains about 1.0 mol[Mg3Fe(II)Fe(III) (OH) 10 ] HCO3 composition.

[0086] Prepare 1.0 L of an aqueous solution containing 3.0 mol / L Mg(NO3)2 and 1.0 mol / L Mn(NO3)2; add 25 g of graphite powder and 15 g of acetylene black under sufficient stirring to form a suspension; then slowly add 4.0 L of an aqueous solution containing 1.0 mol / L Na2CO3 under sufficient stirring and with clean air introduced at an air flow rate of not less than 3.0 L / Min; this process lasts for more than 2 hours; then filter the suspension under stirring, separate the precipitate and wash it once with deionized water, add it to 1.2 L of a solution with a concentration of 1.0 mol / L Na2CO3, stir it for 2 hours, and filter the precipitate to obtain a positive electrode material, which contains about 1.0 mol [Mg3Mn(OH)8] CO3.

[0087] 300 mL of an aqueous solution containing 0.3 mol / L Na2CO3 and 0.3 mol / L NaHCO3 was prepared as an electrolyte, and the prepared negative electrode material and positive electrode material were uniformly mixed with half of the electrolyte respectively.

[0088] The prepared negative electrode material and electrolyte mixture and the positive electrode material and electrolyte mixture were respectively evenly coated on a 30cm*30cm conductive graphite plate, separated by non-woven fabric, and the active materials were symmetrically assembled inwards into a test battery unit.

[0089] The test battery cell was first discharged at a rate of 5C. After the redox reaction of the electrode material and the ion exchange between the electrode material and the electrolyte, the negative electrode material generated [Mg3Fe(III)2(OH) 10 ]CO3 component, and after discharge, the positive electrode material generates [Mg3Mn(OH)8]HCO3 component. Then the test battery cell was subjected to a charge and discharge cycle experiment at a 5C rate.

[0090] Example 2

[0091] A carbonate (Fe, Mn) hydrogen ion battery is prepared by the following method:

[0092] Prepare 1.0 L of an aqueous solution containing 2.0 mol / L MgSO4, 1.0 mol / L FeSO4, and 0.5 mol / L Al2(SO4)3; add 15 g of graphite powder and 20 g of acetylene black under sufficient stirring to form a suspension, then add 4.5 L of an aqueous solution containing 1.0 mol / L Na2CO3 under sufficient stirring, filter under stirring, separate the precipitate, soak it in an aqueous solution containing 0.5 mol / L NaHCO3 for 3 h and wash it, and use the resulting precipitate as the negative electrode material; the precipitate contains about 1.0 mol [Mg2Fe(II)Al(OH)8]HCO3.

[0093] Prepare 1.0 L of an aqueous solution containing 2.0 mol / L MgSO4 and 1.0 mol / L MnSO4; add 15 g of graphite powder and 20 g of acetylene black under sufficient stirring to form a suspension; then slowly add 1.0 L of an aqueous solution containing 1.0 mol / L Na2CO3 and 4.0 mol / L NaOH under sufficient stirring and with clean air introduced at an air flow rate of not less than 3.0 L / Min; this process lasts for more than 2 hours; then filter the suspension under stirring to separate the precipitate, wash it once with deionized water, add it to 1.2 L of a solution with a concentration of 1.0 mol / L Na2CO3, stir it for 2 hours, and filter the precipitate to obtain a positive electrode material, the precipitate containing about 1.0 mol [Mg2Mn(OH)6]CO3.

[0094] Prepare 300 mL of an aqueous solution containing 0.5 mol / L Na2CO3, 0.3 mol / L NaHCO3, and 0.03 mol / L sodium benzenesulfonate as an electrolyte, and evenly mix the prepared negative electrode material and positive electrode material with half of the electrolyte respectively.

[0095] The prepared negative electrode material and electrolyte mixture and the positive electrode material and electrolyte mixture were respectively evenly coated on 30cm*30cm conductive graphite felt, separated by PVDF porous membrane, and the active materials were symmetrically assembled inwardly into a test battery unit.

[0096] The test battery cell was first discharged at a rate of 5C. After the redox reaction of the electrode material and the ion exchange between the electrode material and the electrolyte, the negative electrode material generated [Mg2Fe(III)Al(OH)8]CO3 after discharge, and the positive electrode material generated [Mg2Mn(OH)6]HCO3 after discharge.

[0097] The test battery cell was then subjected to a charge and discharge cycle experiment at a 5C rate.

[0098] Example 3

[0099] A carbonate (Fe, Mn) hydrogen ion battery is prepared by the following method:

[0100] Prepare 1.0 L of an aqueous solution containing 2.0 mol / L MgSO4, 1.0 mol / L FeSO4, and 0.25 mol / L Al2(SO4)3; add 20 g of graphite powder and 20 g of acetylene black under full stirring to form a suspension, then add 3.75 L of an aqueous solution containing 1.0 mol / L Na2CO3 under full stirring, filter under stirring, separate the precipitate and wash with deionized water, and use the obtained precipitate as the negative electrode material; the precipitate contains about 1.0 mol [Mg2Fe (II) Al 0.5 (OH)7] (HCO3) 0.5 ingredients.

[0101] Prepare 1.0 L of an aqueous solution containing 2.0 mol / L MgSO4 and 1.0 mol / L MnSO4; add 20 g of graphite powder and 20 g of acetylene black to form a suspension while fully stirring, then slowly add 3.0 L of an aqueous solution containing 1.0 mol / L Na2CO3 while fully stirring and passing clean air at an air flow rate of not less than 3.0 L / Min. This process lasts for more than 1 hour, and then filter the suspension while stirring, separate the precipitate and wash it once with deionized water, add it to 1.2 L of a solution with a concentration of 1.0 mol / L Na2CO3, stir it for 2 hours, and filter the precipitate to obtain a positive electrode material, which contains about 1.0 mol [Mg2Mn (OH) 6] CO3.

[0102] Prepare 300 mL of an aqueous solution containing 0.4 mol Na2CO3, 0.4 mol NaHCO3, and 0.03 mol / L sodium benzenesulfonate as an electrolyte; and evenly mix the prepared negative electrode material and positive electrode material with half of the electrolyte respectively.

[0103] The prepared negative electrode material and electrolyte mixture and the positive electrode material and electrolyte mixture were respectively evenly coated on 10cm*60cm conductive graphite felt, separated by PE porous membrane, and the active materials were symmetrically assembled inward to form a test battery unit.

[0104] The test battery cell was first discharged at a rate of 5C. After the redox reaction of the electrode material and the ion exchange between the electrode material and the electrolyte, the negative electrode material generated [Mg2Fe (III) Al 0.5(OH)7] (CO3) 0.75 Component, after discharge, the positive electrode material generates [Mg2Mn(OH)6] HCO3 component.

[0105] The test battery cell was then subjected to a charge and discharge cycle experiment at a 5C rate.

[0106] Example 4

[0107] A carbonate (Fe, Mn) hydrogen ion battery is prepared by the following method:

[0108] Prepare 1.0 L of an aqueous solution containing 1.0 mol / L MgSO4, 1.0 mol / L FeSO4, and 0.25 mol / L Al2(SO4)3; add 10 g of graphite powder and 10 g of acetylene black under full stirring to form a suspension, then add 2.75 L of an aqueous solution containing 1.0 mol / L Na2CO3 under full stirring, filter under stirring, separate the precipitate and wash it with deionized water, and use the precipitate as the negative electrode material; the precipitate contains about 1.0 mol [MgFe(II)Al 0.5 (OH)5] (HCO3) 0.5 ingredients.

[0109] Prepare 1.0 L of an aqueous solution containing 1.0 mol / L MgSO4 and 1.0 mol / L MnSO4; add 10 g of graphite powder and 10 g of acetylene black under sufficient stirring to form a suspension, then slowly add 2.0 L of an aqueous solution containing 1.0 mol / L Na2CO3 under sufficient stirring and passing clean air at an air flow rate of not less than 3.0 L / Min. This process lasts for more than 1 hour, and then filter the suspension under stirring, separate the precipitate and wash it once with deionized water, and filter the precipitate to obtain a positive electrode material, which contains about 1.0 mol [MgMn(OH)4]CO3.

[0110] Prepare 300 mL of an aqueous solution containing 0.5 mol Na2CO3, 0.5 mol NaHCO3, and 0.03 mol / L sodium dodecylbenzene sulfonate as an electrolyte; uniformly mix the prepared negative electrode material and positive electrode material with half of the electrolyte respectively, and let stand for more than 9 hours.

[0111] The prepared negative electrode material and electrolyte mixture and the positive electrode material and electrolyte mixture were respectively evenly coated on a 10cm*50cm conductive graphite mesh, separated by a PVDF porous membrane, and the active materials were symmetrically assembled inwardly into a test battery unit.

[0112] The test battery cell was first discharged at a rate of 5C. After the redox reaction of the electrode material and the ion exchange between the electrode material and the electrolyte, the negative electrode material generated [MgFe(III)Al 0.5 (OH)5] (CO3) 0.75 Component, after discharge, the positive electrode material generates [MgMn(OH)4] HCO3 component.

[0113] The test battery cell was then subjected to a charge and discharge cycle experiment at a 5C rate.

[0114] Example 5

[0115] A carbonate (Fe, Mn) hydrogen ion battery is prepared by the following method:

[0116] Prepare 1.0 L of an aqueous solution containing 0.8 mol / L MgSO4, 0.2 mol / L ZnSO4, 1.0 mol / L FeSO4, and 0.25 mol / L Al2(SO4)3; add 10 g of graphite powder and 15 g of acetylene black under full stirring to form a suspension, then add 2.75 L of an aqueous solution containing 1.0 mol / L Na2CO3 under full stirring, filter under stirring, separate the precipitate and wash it with deionized water, and use the precipitate as the negative electrode material; the precipitate contains about 1.0 mol [Mg 0.8 Zn 0.2 Fe(II)Al 0.5 (OH)5](HCO3) 0.5 ingredients.

[0117] Prepare 1.0 L of an aqueous solution containing 0.8 mol / L MgSO4, 0.2 mol / L ZnSO4, and 1.0 mol / L MnSO4; add 10 g of graphite powder and 15 g of acetylene black under sufficient stirring to form a suspension; then slowly add 2.0 L of an aqueous solution containing 1.0 mol / L Na2CO3 under sufficient stirring and with clean air introduced at an air flow rate of not less than 3.0 L / Min; this process lasts for more than 1 hour; then filter the suspension under stirring, add 1.0 L of a solution with a concentration of 1.0 mol / L Na2CO3, stir for 2 hours, separate the precipitate, wash it once with deionized water, and filter the precipitate to obtain a positive electrode material. The precipitate contains about 1.0 mol [Mg 0.8 Zn 0.2 Mn(OH)4]CO3.

[0118] Prepare 300 mL of an aqueous solution containing 0.6 mol K2CO3, 0.6 mol KHCO3, and 0.03 mol / L potassium benzene disulfonate as an electrolyte; and evenly mix the prepared negative electrode material and positive electrode material with half of the electrolyte respectively.

[0119] The prepared negative electrode material and electrolyte mixture and the positive electrode material and electrolyte mixture were respectively evenly coated on 10cm*50cm conductive carbon cloth, separated by filter paper, and the active materials were symmetrically assembled inward to form a test battery unit.

[0120] The test battery cell was first discharged at a rate of 5C. After the redox reaction of the electrode material and the ion exchange between the electrode material and the electrolyte, the negative electrode material generated [MgFe(III)Al 0.5 (OH)5] (CO3) 0.75 Component, after discharge, the positive electrode material generates [MgMn(OH)4] HCO3 component.

[0121] The test battery cell was then subjected to a charge and discharge cycle experiment at a 5C rate.

[0122] Example 6

[0123] An electrode material for a carbonate (Fe, Ni) hydrogen ion battery is prepared by the following method:

[0124] Prepare 1.0 L of an aqueous solution containing 3.0 mol / L Mg(NO3)2 and 2.0 mol / L Fe(NO3)3; add 25 g of graphite powder and 15 g of acetylene black under full stirring to form a suspension, then add 6.0 L of an aqueous solution containing 1.0 mol / L Na2CO3 under nitrogen protection and full stirring, separate the precipitate and wash it once with deionized water, add 1.0 L of a 1.0 mol / L Na2CO3 solution and stir it for 2 h, then filter the precipitate to use as the negative electrode material; the precipitate contains about 1.0 mol[Mg3Fe(III)2(OH) 10 ]CO3 component.

[0125] Prepare 1.0 L of an aqueous solution containing 3.0 mol / L Mg(NO3)2, 1.0 mol / L Ni(NO3)2, and 1.0 mol / L Fe(NO3)3; add 25 g of graphite powder and 15 g of acetylene black under full stirring to form a suspension; then add 5.5 L of an aqueous solution containing 1.0 mol / L Na2CO3 under full stirring; filter the suspension under stirring, separate the precipitate, wash it once with deionized water, and filter the precipitate to obtain a positive electrode material. The precipitate contains about 1.0 mol [Mg3Ni(II) Fe(III)(OH)10 ]HCO3 composition.

[0126] 300 mL of an aqueous solution containing 0.2 mol / L Na2CO3 and 0.1 mol / L NaHCO3 was prepared as an electrolyte, and the prepared negative electrode material and positive electrode material were uniformly mixed with half of the electrolyte respectively.

[0127] The prepared negative electrode material and electrolyte mixture and the positive electrode material and electrolyte mixture were respectively evenly coated on a 30cm*30cm conductive graphite plate, separated by non-woven fabric, and the active materials were symmetrically assembled inwards into a test battery unit.

[0128] The test battery cell was charged at 5C for the first time. After the redox reaction of the electrode material and the ion exchange between the electrode material and the electrolyte, the negative electrode material generated [Mg3Fe(II)Fe(III)(OH) 10 ] HCO3 component, after charging, the positive electrode material generates [Mg3Fe(III)Ni(III) (OH) 10 ]CO3 component.

[0129] The test battery cell is then subjected to a discharge and charge cycle experiment at a 5C rate.

[0130] Example 7

[0131] A carbonate (Fe, Ni) hydrogen ion battery is prepared by the following method:

[0132] Prepare 1.0 L of an aqueous solution containing 2.0 mol / L MgSO4, 0.5 mol / L Fe2(SO4)3, and 0.5 mol / L Al2(SO4)3; add 15 g of graphite powder and 20 g of acetylene black under sufficient stirring to form a suspension, then add 5.0 L of an aqueous solution containing 1.0 mol / L Na2CO3 under sufficient stirring, filter while stirring, separate the precipitate, soak it in an aqueous solution containing 1.0 mol / LNa2CO3 for 3 h and wash it, and use the precipitate as the negative electrode material; the precipitate contains about 1.0 mol [Mg2Fe(III)Al(OH)8]CO3.

[0133] Prepare 1.0 L of an aqueous solution containing 2.0 mol / L MgSO4, 1.0 mol / L NiSO4, and 0.5 mol / L Al2(SO4)3; add 15 g of graphite powder and 20 g of acetylene black under sufficient stirring to form a suspension, then add 5.0 L of an aqueous solution containing 1.0 mol / L Na2CO3 under sufficient stirring, separate the precipitate and wash it once with deionized water, add 1.0 L of a solution with a concentration of 1.0 mol / L NaHCO3 and stir it for 2 h, filter and obtain the precipitate as the positive electrode material, which contains about 1.0 mol [Mg2Ni(II)Al(OH)8] HCO3.

[0134] Prepare 300 mL of an aqueous solution containing 0.3 mol / L Na2CO3, 0.3 mol / L NaHCO3, and 0.03 mol / L sodium benzenesulfonate as an electrolyte, and evenly mix the prepared negative electrode material and positive electrode material with half of the electrolyte respectively.

[0135] The prepared negative electrode material and electrolyte mixture and the positive electrode material and electrolyte mixture were respectively evenly coated on 30cm*30cm conductive graphite felt, separated by PVDF porous membrane, and the active materials were symmetrically assembled inwardly into a test battery unit.

[0136] The test battery cell was charged at a 5C rate for the first time. After the redox reaction of the electrode material and the ion exchange between the electrode material and the electrolyte, the negative electrode material generated [Mg2Fe(II)Al(OH)8]HCO3 component after charging, and the positive electrode material generated [Mg2Ni(III)Al(OH)8]CO3 component after charging.

[0137] The test battery cell is then subjected to a discharge and charge cycle experiment at a 5C rate.

[0138] Example 8

[0139] A carbonate (Fe, Ni) hydrogen ion battery is prepared by the following method:

[0140] Prepare 1.0 L of an aqueous solution containing 2.0 mol / L MgSO4, 0.5 mol / L Fe2(SO4)3, and 0.25 mol / L Al2(SO4)3; add 20 g of graphite powder and 20 g of acetylene black under full stirring to form a suspension, then add 4.25 L of an aqueous solution containing 1.0 mol / L Na2CO3 under full stirring, filter under stirring, separate the precipitate and wash with deionized water, soak it in an aqueous solution containing 1.0 mol / L Na2CO3 for 3 h and wash it, filter the precipitate to obtain the negative electrode material; the precipitate contains about 1.0 mol [Mg2Fe(III)Al0.5 (OH)7](CO3) 0.75 ingredients.

[0141] Prepare 1.0 L of an aqueous solution containing 2.0 mol / L MgSO4, 1.0 mol / L NiSO4, and 0.25 mol / L Al2(SO4)3; add 15 g of graphite powder and 20 g of acetylene black under full stirring to form a suspension, then add 3.75 L of an aqueous solution containing 1.0 mol / L Na2CO3 under full stirring, separate the precipitate and wash it once with deionized water, add 1.0 L of a solution with a concentration of 1.0 mol / L NaHCO3 and stir for 2 h, filter and obtain the precipitate as the positive electrode material, which contains about 1.0 mol[Mg2Ni(II)Al 0.5 (OH)7] (HCO3) 0.5 ingredients.

[0142] Prepare 300 mL of an aqueous solution containing 0.5 mol Na2CO3, 0.5 mol NaHCO3, and 0.03 mol / L sodium benzenesulfonate as an electrolyte; uniformly mix the prepared negative electrode material and positive electrode material with half of the electrolyte respectively, and let it stand for more than 9 hours.

[0143] The prepared negative electrode material and electrolyte mixture and the positive electrode material and electrolyte mixture were respectively evenly coated on 10cm*60cm conductive graphite felt, separated by PE porous membrane, and the active materials were symmetrically assembled inward to form a test battery unit.

[0144] The test battery cell was charged at 5C rate for the first time. After the redox reaction of the electrode material and the ion exchange between the electrode material and the electrolyte, the negative electrode material generated [Mg2Fe(II)Al 0.5 (OH)7] (CO3) 0.25 After charging, the positive electrode material generates [Mg2Ni(III)Al 0.5 (OH)7] (HCO3) 1.5 Element.

[0145] The test battery cell is then subjected to a discharge and charge cycle experiment at a 5C rate.

[0146] Example 9

[0147] A carbonate (Fe, Ni) hydrogen ion battery is prepared by the following method:

[0148] Prepare 1.0 L of an aqueous solution containing 1.0 mol / L MgSO4, 0.5 mol / L Fe2(SO4)3, and 0.25 mol / L Al2(SO4)3; add 10 g of graphite powder and 10 g of acetylene black under full stirring to form a suspension, then add 3.25 L of an aqueous solution containing 1.0 mol / L Na2CO3 under full stirring, filter under stirring, separate the precipitate and wash it with deionized water, soak it in an aqueous solution containing 1.0 mol / L Na2CO3 for 3 h and wash it, filter the precipitate to obtain it as the negative electrode material; the precipitate contains about 1.0 mol [MgFe(III) Al 0.5 (OH)5] (CO3) 0.75 ingredients.

[0149] Prepare 1.0 L of an aqueous solution containing 1.0 mol / L MgSO4, 1.0 mol / L NiSO4, and 0.25 mol / L Al2(SO4)3; add 15 g of graphite powder and 20 g of acetylene black under full stirring to form a suspension, then add 2.75 L of an aqueous solution containing 1.0 mol / L Na2CO3 under full stirring, separate the precipitate and wash it once with deionized water, add 1.0 L of a solution with a concentration of 1.0 mol / L NaHCO3 and stir for 2 h, filter and obtain the precipitate as the positive electrode material, which contains about 1.0 mol[MgNi(II)Al 0.5 (OH)5] (HCO3) 0.5 ingredients.

[0150] Prepare 300 mL of an aqueous solution containing 0.5 mol Na2CO3, 0.5 mol NaHCO3, and 0.03 mol / L sodium dodecylbenzene sulfonate as an electrolyte; uniformly mix the prepared negative electrode material and positive electrode material with half of the electrolyte respectively, and let stand for more than 9 hours.

[0151] The prepared negative electrode material and electrolyte mixture and the positive electrode material and electrolyte mixture were respectively evenly coated on a 10cm*50cm conductive graphite mesh, separated by a PVDF porous membrane, and the active materials were symmetrically assembled inwardly into a test battery unit.

[0152] The test battery cell was charged at 5C for the first time. After the redox reaction of the electrode material and the ion exchange between the electrode material and the electrolyte, the negative electrode material generated [MgFe(II)Al 0.5 (OH)5] (HCO3) 0.5 After charging, the positive electrode material generates [MgNi(III)Al 0.5 (OH)5](CO3) 0.75 Element.

[0153] The test battery cell is then subjected to a discharge and charge cycle experiment at a 5C rate.

[0154] Example 10

[0155] A carbonate (Fe, Ni) hydrogen ion battery is prepared by the following method:

[0156] Prepare 1.0 L of an aqueous solution containing 0.8 mol / L MgSO4, 0.2 mol / L ZnSO4, 0.5 mol / L Fe2(SO4)3, and 0.25 mol / L Al2(SO4)3; add 10 g of graphite powder and 15 g of acetylene black under sufficient stirring to form a suspension, then add 3.25 L of an aqueous solution containing 1.0 mol / L Na2CO3 under sufficient stirring, filter under stirring, separate the precipitate and wash it with deionized water, soak it in an aqueous solution containing 1.0 mol / L Na2CO3 for 3 h and wash it, filter the precipitate to obtain it as the negative electrode material; the precipitate contains 1.0 mol [Mg 0.8 Zn 0.2 Fe(III)Al 0.5 (OH)5] (CO3) 0.75 ingredients.

[0157] Prepare 1.0 L of an aqueous solution containing 0.8 mol / L MgSO4, 0.2 mol / L ZnSO4, 1.0 mol / L NiSO4, and 0.25 mol / L Al2(SO4)3; add 15 g of graphite powder and 20 g of acetylene black under sufficient stirring to form a suspension, then add 2.75 L of an aqueous solution containing 1.0 mol / L Na2CO3 under sufficient stirring, separate the precipitate and wash it once with deionized water, add 1.0 L of a solution with a concentration of 1.0 mol / L NaHCO3 and stir for 2 h, filter and obtain the precipitate as the positive electrode material, which contains about 1.0 mol [Mg 0.8 Zn 0.2 Ni(II)Al 0.5 (OH)5] (HCO3) 0.5 ingredients.

[0158] Prepare 300 mL of an aqueous solution containing 0.6 mol K2CO3, 0.6 mol KHCO3, and 0.03 mol / L potassium benzene disulfonate as an electrolyte; uniformly mix the prepared negative electrode material and positive electrode material with half of the electrolyte respectively, and let it stand for more than 9 hours.

[0159] The prepared negative electrode material and electrolyte mixture and the positive electrode material and electrolyte mixture were respectively evenly coated on 10cm*50cm conductive carbon cloth, separated by filter paper, and the active materials were symmetrically assembled inward to form a test battery unit.

[0160] The test battery cell was charged at 5C rate for the first time. After the redox reaction of the electrode material and the ion exchange between the electrode material and the electrolyte, the negative electrode material generated [Mg 0.8 Zn 0.2 Fe(II)Al 0.5 (OH)5](HCO3) 0.5 Composition, after charging, the positive electrode material generates [Mg 0.8 Zn 0.2 Ni(III)Al 0.5 (OH)5] (CO3) 0.75 Element.

[0161] The test battery cell is then subjected to a discharge and charge cycle experiment at a 5C rate.

[0162] Embodiment 11

[0163] A carbonate (Fe, Ni) hydrogen ion battery is prepared by the following method:

[0164] Prepare 1.0 L of an aqueous solution containing 0.1 mol / L MgSO4, 0.1 mol / L ZnSO4, 0.5 mol / L Fe2(SO4)3, and 0.1 mol / L Al2(SO4)3; add 10 g of graphite powder and 15 g of acetylene black under sufficient stirring to form a suspension, then add 2.0 L of an aqueous solution containing 1.0 mol / L Na2CO3 under sufficient stirring, filter under stirring, separate the precipitate and wash it with deionized water, and soak it in an aqueous solution containing 1.0 mol / L Na2CO3 for 3 h and wash it, and separate the precipitate as the negative electrode material; the precipitate contains 1.0 mol [Mg 0.1 Zn 0.1 Fe(III)Al 0.2 (OH) 2.8 ] (CO3) 0.6 ingredients.

[0165] Prepare 1.0 L of an aqueous solution containing 0.1 mol / L MgSO4, 0.1 mol / L ZnSO4, 1.0 mol / L NiSO4, and 0.1 mol / L Al2(SO4)3; add 15 g of graphite powder and 20 g of acetylene black under sufficient stirring to form a suspension, then add 1.5 L of an aqueous solution containing 1.0 mol / L Na2CO3 under sufficient stirring, separate the precipitate and wash it once with deionized water, add 1.0 L of a solution with a concentration of 1.0 mol / L NaHCO3 and stir it for 2 h, filter the precipitate to obtain a positive electrode material, which contains about 1.0 mol [Mg 0.1 Zn 0.1 Ni(II)Al 0.2 (OH) 2.8 ] (HCO3) 0.2 ingredients.

[0166] Prepare 300 mL of an aqueous solution containing 0.6 mol K2CO3 and 0.6 mol KHCO3 as an electrolyte; evenly mix the prepared negative electrode material and positive electrode material with half of the electrolyte respectively, and let it stand for more than 9 hours.

[0167] The prepared negative electrode material and electrolyte mixture and the positive electrode material and electrolyte mixture were respectively evenly coated on 10cm*50cm conductive carbon cloth, separated by filter paper, and the active materials were symmetrically assembled inward to form a test battery unit.

[0168] The test battery cell was charged at 5C rate for the first time. After the redox reaction of the electrode material and the ion exchange between the electrode material and the electrolyte, the negative electrode material generated [Mg 0.1 Zn 0.1 Fe(II)Al 0.2 (OH) 2.8 ](CO3) 0.1 Composition, after charging, the positive electrode material generates [Mg 0.1 Zn 0.1 Ni(III)Al 0.2 (OH) 2.8 ] (HCO3) 1.2 Element.

[0169] The test battery cell is then subjected to a discharge and charge cycle experiment at a 5C rate.

[0170] Comparative Example 1

[0171] Commercially available lithium batteries

[0172] Manufacturer: Shenzhen Hailei New Energy Co., Ltd.

[0173] Model: HL48300

[0174] Nominal voltage: 51.2V, nominal capacity: 300Ah

[0175] Cycle times: >2000 times, 50°C

[0176] Combination: Single cell, Battery type: Square lithium iron phosphate battery,

[0177] Weight: 119kg

[0178] Comparative Example 2

[0179] Commercially available lead-acid batteries

[0180] Manufacturer: Guangdong Mingweiteng New Energy Co., Ltd.

[0181] Specifications: DC12-12

[0182] Nominal voltage: 12V

[0183] Nominal capacity: 7AH

[0184] Float charge life: 3-4 years

[0185] Number of cycles: 800

[0186] Weight: 3.2 kg

[0187] Product size: 150*64*96mm

[0188] Comparative Example 3

[0189] All-vanadium flow battery

[0190] Manufacturer: Dalian Rongke Energy Storage Group Co., Ltd.

[0191] Specifications: TPower7

[0192] Number of cycles: 16,000 times (20 years)

[0193] Rated capacity 1000~3000 kWh

[0194] Rated power: 500 kW

[0195] Total weight: 140 tons

[0196] Dimensions: 9.1m×5.8m×5.8m (L*W*H)

[0197] Performance Testing

[0198] The test conditions and methods are as follows:

[0199] The batteries of the above-mentioned embodiments and comparative examples were subjected to charge and discharge tests at a rate of 5C to test energy density and cycle life, and the active material cost of each test example was estimated according to the prices of commercially available bulk chemicals.

[0200] Record the battery voltage, the number of cycles at which the battery capacity decays to 80% of the rated capacity, the charge and discharge energy efficiency, and the cost of active materials. The cost of raw materials is referenced in the following table:

[0201] The results are as follows:

[0202]

[0203] From the above table, combined Figure 2 It can be seen that the number of cycles of the carbonate (Fe, Mn) hydrogen ion batteries (Examples 1-3) of the present invention far exceeds that of the lead-acid batteries (Comparative Example 2) and the lithium-ion batteries (Comparative Example 1), and is slightly lower than that of the all-vanadium liquid flow batteries (Comparative Example 3); although the energy density of the carbonate (Fe, Mn) hydrogen ion batteries (Examples 1-3) developed by the present invention is lower than that of the lithium-ion batteries, it is equivalent to that of the lead-acid batteries and higher than that of the all-vanadium liquid flow batteries; cost accounting shows that the unit energy storage cost of the carbonate (Fe, Mn) hydrogen ion batteries (Examples 1-3) developed by the present invention is only equivalent to 70% of that of the lithium-ion batteries and 35% of that of the all-vanadium liquid flow batteries, and the charge and discharge energy efficiency is higher than that of the lead-acid batteries and the all-vanadium liquid flow batteries, and therefore has broad application prospects in the field of large-scale power energy storage. Examples 4-5 further increase the content ratio of Fe and Mn elements in the battery, and the number of cycles is reduced compared with Comparative Examples 1 and 3, but the energy density is further improved compared with Comparative Examples 2-3. Among them, Example 5 increases the number of cycles to a certain extent compared with Example 4 by adding the Zn element, and is suitable for some specific application scenarios that require higher energy density.

[0204] Combining from the above table Figure 3 It can be seen that the number of cycles of the carbonate (Fe, Ni) hydrogen ion batteries (Examples 6-8) developed by the present invention far exceeds that of lead-acid batteries and lithium-ion batteries, and is equivalent to that of all-vanadium liquid flow batteries; although the energy density of the carbonate (Fe, Ni) hydrogen ion batteries (Examples 6-8) developed by the present invention is lower than that of lithium-ion batteries, it is higher than that of lead-acid batteries and all-vanadium liquid flow batteries; cost accounting shows that the unit energy storage cost of the carbonate (Fe, Ni) hydrogen ion batteries (Examples 6-8) developed by the present invention is only equivalent to 90% of that of lithium-ion batteries and 60% of that of all-vanadium liquid flow batteries, and the charge and discharge energy efficiency is higher than that of lead-acid batteries and all-vanadium liquid flow batteries, and therefore has broad application prospects in the field of large-scale power energy storage.

[0205] Examples 9-11 further increase the content ratio of Fe and Ni elements, and the number of cycles is reduced compared with Examples 6-8, but the energy density is further improved compared with Examples 2-3. Among them, Example 10 increases the number of cycles to a certain extent and maintains a relatively high energy density compared with Example 9 by adding the Zn element. Although the number of cycles of Example 11 is reduced, the energy density is further improved, which is suitable for some specific application scenarios that require higher energy density.

[0206] In summary, it can be seen that the carbonate-based hydrogen ion battery developed by the present invention utilizes the variable valence characteristics of transition metal elements such as iron, manganese, and nickel, which has excellent comprehensive performance and is suitable for large-scale low-cost chemical energy storage. It overcomes the problems of low charge and discharge cycles of lead-acid batteries, hydrogen evolution corrosion, and heavy metal environmental pollution in the battery recycling process; it overcomes the problem of potential safety hazards in lithium batteries due to the use of organic electrolytes, as well as the problem of high costs and limited production due to the use of expensive metal elements such as cobalt and lithium; it also overcomes the damage to electrode materials during the embedding, de-embedding, and shuttling of sodium ions in sodium ion batteries, thereby reducing the number of cycles and service life of the battery. It has the advantages of low cost, high number of charge and discharge cycles, long service life, and high charge and discharge power, and is suitable for industrial production, especially for large-scale power energy storage applications.

Claims

1. A carbonate-based hydrogen ion battery, characterized in that: The positive electrode active material and the negative electrode active material of the hydrogen ion battery are basic carbonates or bicarbonates containing variable-valence transition metal elements, and the aqueous electrolyte is a buffer solution containing soluble carbonates or bicarbonates; The oxidation-reduction electrochemical reaction of the active elements in the hydrogen ion battery during the charge and discharge process is: XHCO3 – e => X’CO3 + H + (a) X’CO3 + H + + e => XHCO3(b) Wherein, X and X' are corresponding basic cations of adjacent valence states containing variable valence transition metal elements; The variable valence transition metal element is iron, manganese or nickel; The negative electrode active material of the hydrogen ion battery is an alkaline carbonate or bicarbonate containing iron, and the positive electrode active material of the hydrogen ion battery is an alkaline carbonate or bicarbonate containing manganese or nickel; The aqueous electrolyte contains carbonate with a concentration of 0.01-5 mol / L or bicarbonate with a concentration of 0.01-5 mol / L, or a mixture of the two; the corresponding cation is Na + , K + One or a mixture of both.

2. A carbonate-based hydrogen ion battery according to claim 1, characterized in that: The negative electrode active material of the hydrogen ion battery is a basic carbonate or bicarbonate containing iron and magnesium elements, forming an Fe(III / II) electrode pair; the chemical formula of the negative electrode material of the basic carbonate or bicarbonate containing iron and magnesium elements includes: Fe(III)-CO3:[Mg x Fe(III) 1+y (OH) 2(1+x+y) ](CO3) (1+y) / 2 , where 0 <x≤10,0≤y≤1; Alternatively, Fe(II)-HCO3:[Mg x Fe(II)Fe(III) y (OH) 2(1+x+y) ](HCO3) y , where 0 <x≤10,0<y≤1。 3. A carbonate-based hydrogen ion battery according to claim 1, characterized in that: The positive electrode active material of the hydrogen ion battery is a basic carbonate or bicarbonate containing manganese and magnesium elements, forming a Mn (IV / III) electrode pair. The chemical formula of the positive electrode material containing the basic carbonate or bicarbonate containing manganese and magnesium elements includes: Mn(IV)-CO3:[Mg x Mn(IV)(OH) 2(1+x) ]CO3, of which 0 <x≤10; Alternatively, Mn(III)-HCO3:[Mg x Mn(III) (OH) 2(1+x) ]HCO3, of which 0 <x≤10。 4. A carbonate-based hydrogen ion battery according to claim 1, characterized in that: The positive electrode active material of the hydrogen ion battery is a basic carbonate or bicarbonate containing nickel and magnesium elements, forming a Ni (III / II) electrode pair. The chemical formula of the positive electrode material of the basic carbonate or bicarbonate containing nickel and magnesium elements includes: Ni(III)-CO3:[Mg x Ni(III) 1+y (OH) 2(1+x+y) ](CO3) (1+y) / 2 , where 0 <x≤10,0≤y≤1; Alternatively, Ni(II)-HCO3:[Mg x Ni(II)Ni(III) y (OH) 2(1+x+y) (HCO3) y , where 0 < x ≤ 10, 0 < y ≤ 1; or Fe partially replaces Ni: Ni(III)-CO3:[Mg x Ni(III)Fe(III) y (OH) 2(1+x+y) ](CO3) (1+y) / 2 , where 0≤x≤10, 0≤y≤1; Ni(II)-HCO3:[Mg x Ni(II)Fe(III) y (OH) 2(1+x+y) ] (HCO3) y , where 0 <x≤10,0<y≤1。 5. A carbonate-based hydrogen ion battery according to claim 1, characterized in that: The positive electrode active material and the negative electrode active material of the hydrogen ion battery are further added with basic carbonate or bicarbonate containing Al or Zn elements, and the molar ratio of basic carbonate or bicarbonate to the variable valence transition metal element X is Al: Zn: X = 0~1: 0~1: 1, and the variable valence transition metal element is Fe, Mn or Ni.

6. A carbonate-based hydrogen ion battery according to claim 1, characterized in that: The basic carbonate or bicarbonate containing variable valence transition metal elements also contains benzene sulfonate, benzene disulfonate or alkyl benzene sulfonate and the corresponding Na + , K + cation.

7. A carbonate-based hydrogen ion battery according to claim 1, characterized in that: The basic carbonate or bicarbonate containing a variable-valence transition metal element is also mixed with a conductive carbon material, and the mass ratio of the basic carbonate or bicarbonate containing a variable-valence transition metal element to the conductive carbon material is 1:0.01-0.5; The conductive carbon material is acetylene black, graphite or a mixture of the two.

8. A method for preparing a carbonate-based hydrogen ion battery as claimed in claim 1, characterized in that: The positive electrode active material and the negative electrode active material are mixed with an aqueous electrolyte respectively, and are coated on a carbon electrode material collector respectively to obtain a positive electrode material and a negative electrode material, and the positive electrode material and the negative electrode material are separated by a corrosion-resistant porous material to obtain a single cell, and a plurality of single cells are stacked and assembled in parallel or rolled into a column to obtain a battery core pack, which is then encapsulated in a corrosion-resistant battery shell to obtain a hydrogen ion battery pack.

Citation Information

Patent Citations

  • Redox and ion-adsorbtion electrodes and energy storage devices

    CN112005408A

  • Aqueous manganese dioxide-metal secondary battery

    CN112952212A

  • Aqueous manganese ion battery and preparation process thereof

    CN115051046A

Cited By

  • A hydrogen ion battery based on titanium negative electrode and preparation method thereof

    CN120413820B